ANALISIS SISTEM PENGENDALIAN INTERNAL PADA SIKLUS PENDAPATAN DAN PENGELUARAN KAS (Studi Kasus pada Rumah Sakit Wava Husada Kabupaten Malang) - DIGAR HASTITORO (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
The research has the aim to analyze the internal control system, particularly the system of cash revenue and expenditure, of Wava Husada Hospital. The research is qualitative descriptive by comparing the internal control system in Wava Husada Hospital against the effectiveness of the internal control system according to the Committee of Sponsoring Organizations of the Treadway Commission (COSO), consisting of control environment, risk assessment, control activities, information and communication, and monitoring. Based on the results of the research, it was found that internal control related to the cycle of income and expenditure is still not effective. There are still problems, including (1) the absence of segregation of duties in the billing administration section, which should have a clear separation of duties so that the potential for fraud can be avoided; (2) the provision of general accounts receivable lacks authorization from the financial section, and thus the general receivables should be given authorization so that someone is responsible; (3) in providing general accounts, the patient's identity is sometimes not examined first, which causes the problematic collection of general accounts receivable, as in providing receivables, the inclusion of identity must be clear in order to facilitate the billing process; and (4) the whistleblowing system has not run well.Keywords: internal control system, revenue cycle, expenditure cycle, COSO, Hospital